2020
DOI: 10.30900/kafkasegt.680563
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of mathematics achievements of middle school students in terms of parental support

Abstract: Ebeveyn desteğinin genel olarak eğitimde etkili olduğu kadar özelde de matematik eğitiminde göz önünde bulundurulması gereken bir konu olduğu artık araştırmalarca desteklenmektedir. Ancak bu desteğin nasıl olması gerektiği konusunda sınırlı sayıda araştırma mevcuttur. Araştırmalar genelde korelasyonel çalışmalar olup uygulamaya dönük az sayıda çalışmaya rastlanılmıştır. Bu bakımdan bu çalışmada uygulama destekli akademik başarı incelemek istenmiştir. Bu doğrultuda çalışmanın amacı, ebeveyn desteğinin ortaokul … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In this study, the development of parents with a higher level of education was more positive than other parents. In previous studies (Kutluca & Aydın, 2010;Morkoyunlu & Konyalıoğlu, 2020;Yenilmez, 2006;Yenilmez et al, 2006), it was revealed that parents with higher education levels were more active and more effective in their participation in their student's education. Therefore, Yenilmez (2006) stated that out-ofschool support for students can also be increased by increasing the parents' educational level.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, the development of parents with a higher level of education was more positive than other parents. In previous studies (Kutluca & Aydın, 2010;Morkoyunlu & Konyalıoğlu, 2020;Yenilmez, 2006;Yenilmez et al, 2006), it was revealed that parents with higher education levels were more active and more effective in their participation in their student's education. Therefore, Yenilmez (2006) stated that out-ofschool support for students can also be increased by increasing the parents' educational level.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…Previous studies have shown that parental involvement increases students' academic achievement (Becker & Epstein, 1981, 1982a, 1982bEpstein, 1983Epstein, , 1985Epstein, , 2016Epstein, , 2018Epstein & Becker, 1982;Grolnick & Slowiaczek, 1994;Grolnick, Benjet, Kurowski & Apostoleris, 1997;Hill & Tyson, 2009;Knapp, Landers, Liang & Jefferson, 2017;Morkoyunlu & Konyalıoğlu, 2020;Özakça, 2015;Reaburn & Roberts, 2018;Yenilmez, 2006;Yıldırım, 2019). All students thought they would be more successful in mathematics if such parental support were provided throughout the year.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This problem can be solved by increasing mathematics-related experiences starting in the early years and associating these experiences with daily life. Many scientific studies predict the relationship between parental awareness, mathematics education, and mathematics skills [84][85][86]. They report that parents' awareness of mathematics positively affects children's learning and reduces negative feelings, anxiety, and fears about mathematics.…”
Section: Discussionmentioning
confidence: 99%